Public Works and Housing Infrastructure Planning using Environmental Carrying Capacity Consideration:Case Study on Planning Dam Development in Kalimantan Island, Indonesia - Panji Estutama; Mochamad Adhi Kurniawan (The Journal of Indonesia Sustainable Development Planning, 2021)
This article aims to explain how the environmental carrying capacity indicators could benefit public works and housing infrastructure planning. Law No. 32/2009 about environmental protection and management stated that the government is obliged to implement the Strategic Environment Assessment (SEA/KLHS) in the preparation of policies, plans, and/or programs that have the potential to cause environmental impacts and/or risks. This research aims to understand the process of using ecosystem services as part of the environmental carrying capacity. This approach would be relevant to the public works and housing infrastructure planning and is related to the National Medium Term Development Plan (RPJMN) goals in considering the environmental carrying capacity. This means that if the development of infrastructure does not meet the criteria of the environmental carrying capacity, it will cause negative impacts that could lead to futile infrastructures. The process of considering the environmental carrying capacity will be explained in quantitative methodology as an analysis process with a matrix as an overlay result. The overlay result will be interpreted as the basic information on whether a building in that location is feasible or not for carrying capacity conditions. The overlay result will be used as a basis for providing suggestions and recommendations.